2016
DOI: 10.1108/wjemsd-07-2015-0029
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting entrepreneurial intentions among Kuwaitis

Abstract: Purpose – The purpose of this paper is to examine the key influential factors that affect the entrepreneurial intentions of Kuwaiti nationals. Design/methodology/approach – This study was carried out by a survey method, using a questionnaire that targeted all Kuwaiti nationals over 18 who had the possibility of becoming entrepreneurs. The respondents’ perceptions of six antecedents that could influence entrepreneurial intentions were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 49 publications
1
39
1
Order By: Relevance
“…Thus, this presents opportunities for ethnic and migrant entrepreneurship which was traditionally hampered by a complex amalgamation of barriers. Elali and Al-Yacoub (2016) argued that the most significant factor determining whether young immigrants would set up businesses, was the need for achievement factor. The sense of accomplishment enables the migrant entrepreneur to feel a sense of self-worth and contribution to their new communities (Hack-Polay et al., 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, this presents opportunities for ethnic and migrant entrepreneurship which was traditionally hampered by a complex amalgamation of barriers. Elali and Al-Yacoub (2016) argued that the most significant factor determining whether young immigrants would set up businesses, was the need for achievement factor. The sense of accomplishment enables the migrant entrepreneur to feel a sense of self-worth and contribution to their new communities (Hack-Polay et al., 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to empirical research carried out in Spain, such courses develop self-efficacy, pro-activeness and risk-taking competences for attending students [25]. Universities and the entrepreneurial curriculum were found to be the greatest influencers of students' entrepreneurial attitudes in a study conducted among 1500 undergraduate Arab students in government universities [26]. One of the empirical studies conducted among Pakistani university students revealed perceived educational support as the most important factor in developing students' entrepreneurial self-efficacy [27].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Entrepreneurial intention is defined as human behavioural activity that encourages them to pursue information, to develop an idea and to carry out a business plan in order to be an entrepreneur (Tiwari, Bhat, & Tikoria, 2017). Similar from other research, Elali and Al-Yacoub (2016) have claimed that entrepreneurial intention is a person's motivation to start and drive for the introduction of a new commercial venture from the understanding of opportunities and self-confidence towards ability will improve entrepreneurial intention in the future. Thus, from all of the researches have been conducted, it can be concluded that entrepreneurial intention is a condition where someone is equipped with motivation to establish new business and become an entrepreneur.…”
Section: Entrepreneurial Intentionmentioning
confidence: 74%